1971
DOI: 10.1021/ic50101a031
|View full text |Cite
|
Sign up to set email alerts
|

Crystal and molecular structure of tris(glycinato)chromium(III) monohydrate, Cr(C2H4NO2)3.H2O

Abstract: Figure 4.-The coordination polyhedron about the Pr(II1) ion showing the monocapped square-antiprismatic configuration.is bent down toward plane B as can be seen in Figure 3. Since this complex contains constraints of chelating as well as three different kinds of atoms in the coordination sphere, it does not lend itself to detailed analysis of the coordination polyhedron. Day and Hoard2; have noted that the quasi-Cd axis [N(1)-Pr] corresponding to the Cdv symmetry of the idealized monocapped square antiprism mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
26
0

Year Published

1971
1971
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(35 citation statements)
references
References 5 publications
7
26
0
Order By: Relevance
“…On the other hand, it is likely that a higher bioavailability characterizes chromium(III) complexes with amino acids, as naturally existing biomolecules. However, though many chromium-amino acids complexes are known [11][12][13][14][15][16], to date no studies on their kinetics in aqueous solutions or their cytotoxicity were performed. In this work, studies on chromium-glycinato complexes are described.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…On the other hand, it is likely that a higher bioavailability characterizes chromium(III) complexes with amino acids, as naturally existing biomolecules. However, though many chromium-amino acids complexes are known [11][12][13][14][15][16], to date no studies on their kinetics in aqueous solutions or their cytotoxicity were performed. In this work, studies on chromium-glycinato complexes are described.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, studies on chromium-glycinato complexes are described. Two compounds, [Cr(gly) 3 ] and [Cr(gly) 2 (OH)] 2 , were obtained earlier [11][12][13] and their structures were determined by X-ray diffraction. The tris-complex was found to be the fac-isomer [12].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been found that the crystal of f~c -C r ( g l y )~. H~O has a threedimensional network of intermolecular hydrogen bonds between the chelate molecules, and that the water molecule in the crystal also serves to link two molecules of the chelate (18). These facts suggest that the dissolution of f a c -C~( g l y )~ in W results from hydrophilic hydration composed of the hydrogen bond between the carboxylic andlor amino groups of the chelate and water molecules.…”
Section: Discussionmentioning
confidence: 99%